Associations Between Pregnancy-related Weight Variation, Prenatal Care Factors and Infant Birth Weight - (:unkn) unknown (My University, 2023)
Background: Variations in maternal weight before and during pregnancy are intricately connected to infant birth weight (IBW). More than 50% of women enter pregnancy at a higher-than-normal body mass index (BMI) and gain outside of the recommended weight during pregnancy based on the 2009 IOM gestational weight gain (GWG) guidelines, impacting IBW. This is a concern because infants born too small or large are at risk for perinatal complications and future health problems. The study explored women's characteristics and prenatal care factors linked to pregnancy-related weight variations such as BMI, GWG, and IBW and the relationships between these three factors within the IOM GWG guidelines. Methods: This study employed a retrospective descriptive-correlational design utilizing PeriData.Net®. This dataset includes clinical data on each delivery at one of the Midwest urban hospitals. The PeriData.Net® data has maternal demographics, medical history, and maternal and infant information on delivery. A generalized multinomial model was used to identify how women’s characteristics, prenatal care factors, and BMI were associated with the odds of inadequate or excessive GWG according to the 2009 IOM guidelines. Results: A total of 8,699 women (>18 years) with a live singleton birth were included in the study. Regardless of pre-pregnancy BMI, nearly half (48.4%) of all women gained excessive weight during pregnancy. Notably, white (52%) and Black (43.5%) women in the overweight or obese BMI categories were more likely to have inadequate or excessive GWG and deliver an SGA or an LGA infant, Race, parity, education, BMI, parity, health insurance, nativity, and prenatal care visits had a significant effect on the odds of observing inadequate or excessive GWG compared with recommended GWG. Overall, 27.8% of this sample met the IOM-recommended GWG guidelines, regardless of BMI. Nearly a quarter (23.8%) of the women did not meet adequate gestational weight gain. Race, parity, education, BMI, age, and marital status significantly increased the odds of delivering small-for-gestational-age (SGA) or large-for-gestational-age (LGA) infants compared to an appropriate-for-gestational-age (AGA) infant. Black or African American, unmarried, and inadequate GWG significantly increased the odds of SGA infants. Increased woman’s age, number of prenatal visits, overweight and obesity prior to pregnancy, high gestational weight gain, and multiple pregnancies significantly increased the odds of having an LGA infant. Conclusions: This study shows that despite 2009 IOM national guidelines, much variation exists in the weight gain by women with normal and high BMI prior to pregnancy, as only 28% met the recommended weight gain. Findings from this study indicate that (a) population diversity, both in BMI and GWG, needs specific guidelines; (b) implementation of the guidelines needs to be evaluated to reflect current women’s characteristics and prenatal care factors that impact adherence to IOM guidelines, and (c) guidelines must address specific weigh gain ranges for each obesity class. Future guidelines should reflect the diversity of the population and ways to optimize GWG and likely call for further research to provide insights into recommended GWG during pregnancy.
Keywords: bpdy mass index; gestational weight gain; Infant birth weight; obesity; prenatal care factors; women characteristics